2000
DOI: 10.1007/s002400000116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p21 WAF1/CIP1 and cyclin D 1 expression in the progression of superficial bladder cancer

Abstract: Immunoreactivity of p21WAF1/CIP1 and cyclin D1 proteins was assessed in a cohort of 207 patients with superficial (pTa-pT1) bladder cancer followed up for a mean of 4.9 years. The results of the immunostainings were compared with T category, WHO grade, tumor cell proliferation rate (MIB-1 score), the expressions of p53 and bcl-2 as well as survival. Sixty-eight percent and 75% of the tumors were p21WAF1/CIP1 positive (> or = 5% of cells positive) and cyclin D1 positive (> or = 10% of cells positive), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
2
23
1
3
Order By: Relevance
“…Cyclin D1 expression in our study showed that lower expression is associated with poorly-differentiated tumours. This finding is consistent with the results of other studies [6,[8][9][10][11]14]. In addition, we found a lower expression in pT2-4 tumours compared with pTa and pT1 according to the findings of other investigators [6,8,11,14].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Cyclin D1 expression in our study showed that lower expression is associated with poorly-differentiated tumours. This finding is consistent with the results of other studies [6,[8][9][10][11]14]. In addition, we found a lower expression in pT2-4 tumours compared with pTa and pT1 according to the findings of other investigators [6,8,11,14].…”
Section: Discussionsupporting
confidence: 83%
“…The relationship between cyclin D1 expression and the risk of subsequent recurrence is controversial. Some investigators found that the overexpression of cyclin D1 correlates with early recurrence in superficial bladder cancer [9,14]. On the other hand, Wagner et al [11] found that cyclin D1 positivity was not linked to the risk of recurrence or tumour progression, either in pTa or in pT1 carcinomas according to the results of our study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…La mayoría de trabajos no la señalan como un factor predictivo independiente en tumores superficiales [24][25][26][27][28] , incluidos aquellos que consideran específicamente los tumores de alto riesgo y T1G3 3, 21 .…”
Section: Inmunohistoquímica De P21unclassified